2005
DOI: 10.1038/sj.ejcn.1602223
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Medgem and Deltatrac resting metabolic rate measurements

Abstract: Objective: The primary aims of this trial were to evaluate the reproducibility of a portable handheld calorimeter (Medgem) in a clinical population, and to compare its measures with a calorimeter in typical use with these patients. Design: Cross-sectional clinical validation study. Setting: Outpatient Clinical Research Center. Subjects: A total of 24 stable home nutrition support patients. Interventions: In random order three measures of resting metabolic rate (RMR) were taken after a 4-h fast, 15 min rest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 18 publications
1
61
0
1
Order By: Relevance
“…Six of the 8 studies indicated that the Gem device performs very comparably (RMR range 0.1-4.0%, interclass reliability range 0.76-0.92) to traditional metabolic carts. The studies conducted by Compher et al (6) and Reeves et al (27) demonstrated that the Gem measures RMR significantly lower (RMR values range from -8.2 to -15.1%) than traditional metabolic carts do. Detailed results from the included comparison studies are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the 8 studies indicated that the Gem device performs very comparably (RMR range 0.1-4.0%, interclass reliability range 0.76-0.92) to traditional metabolic carts. The studies conducted by Compher et al (6) and Reeves et al (27) demonstrated that the Gem measures RMR significantly lower (RMR values range from -8.2 to -15.1%) than traditional metabolic carts do. Detailed results from the included comparison studies are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The Gem has been compared with 4 different metabolic-cart systems. Two of those studies suggest that it measures RMR significantly below the RMR values of metabolic carts (6,27), and the other 6 studies, when adjusting for subject positioning, suggest that it performs similarly to metabolic carts (1, 9, 18, 20, 30, 31, 32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More practical methods for measuring REE are under development and include the use of hand-held calorimeters, although their accuracy compared to standard calorimetry is questionable (Compher et al, 2005;Reeves et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Resting energy expenditure was measured using the BodyGem handheld indirect calorimeter (model 200-0001-01; HealtheTech, Golden, CO, USA), validated against other techniques (Melanson et al, 2004;Compher et al, 2005;Rubenbauer et al, 2006). Fasted blood samples were drawn by trained professionals and sent to a quality-assured pathology laboratory (Southern IML Pathology, Wollongong, Australia).…”
Section: Methodsmentioning
confidence: 99%